Salmonella enterica Serotype Choleraesuis Infection of the Knee and Femur in a Nonbacteremic Diabetic Patient. (28th May 2013) - Sy, Alexander M.; Sandhu, Jagbir; Lenox, Theodore
Abstract : Osteoarticular infections caused by Salmonella are rare. The rates of osteomyelitis and septic arthritis due to Salmonella are estimated to be less than 1% and 0.1%-0.2%, respectively (Kato et al., 2012). Salmonella enterica serotype Choleraesuis is a nontyphoidal Salmonella, highly pathogenic in humans, usually causing septicemic disease with little or no intestinal involvement. Serotype Choleraesuis accounts for a small percentage of published studies of Salmonella infections in the United States. It is not commonly reported in joint fluid and bones in contrast to serotype Enteritidis and Typhi, where a considerable number of cases have been published. Chen et al. in Taiwan found that 21% of bacteremic patients with this infection subsequently develop focal infections such as septic arthritis, pneumonia, peritonitis, and cutaneous abscess (Chen et al., 1999, Chiu et al., 2004). In contrast, our patient presented with localized osteoarticular infection with Salmonella enterica serotype Cholerasuis, but without evidence of bacteremia.